Comparative Analytical Modeling and Performance Investigation of Graphene-Based Super Capacitor with Four Traditional Batteries - Arsal Mehmood (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2021)
Graphene, a magical development of 2004, has revolutionized today's energy storage technologies. It is nothing but a graphite two-dimensional (2D) allotropic pure carbon layer which is derived from a three-dimensional (3D) shape. Since batteries have been the most common storage device from the invention of the first electrical battery by an Italian physicist Alessandro Volta in 1799 A.D but batteries offer many drawbacks, such as length, weight, poor transient response, low power density, and high internal resistance. In this contrast, the impressive and unique properties of graphene supercapacitor such as high peak current, high surface area, high electrical conductivity, low internal resistance, high load current, long life cycle, high power density, low-temperature charging, and discharging make graphene supercapacitor a replacement of traditional energy storage devices and sets trend for the future. This analytical comparative analysis presents an overview between four traditional batteries and graphene-based supercapacitor. For this regard, dynamic models, modeling equations, and an integrated simulation model for batteries and graphene-supercapacitors under MATLAB/Simulink® 2020a environment is developed. In addition, the effect of temperature on battery output and graphene-supercapacitor is also addressed.